Whether Out-of-Bed Activity Restriction in the Early Postoperative Period of PELD Is Beneficial to Therapeutic Efficacy or Reduce Recurrence - Liang, Xiao; Wang, Yexin; Yue, Yaosheng; Li, Yanpeng; Meng, Chunyang (Frontiers in Surgery, 2022)
Objective To detect the influences of postoperative out-of-bed activity restriction on recurrence rate, low back and leg pain, functional rehabilitation after percutaneous endoscopic lumbar discectomy (PELD). Methods In this research, 213 patients with lumbar intervertebral disc herniation (LDH) who underwent PELD were divided into the out-of-bed activity restriction group and out-of-bed activity non-restriction group. The visual analog scale (VAS) and Oswestry disability index (ODI) scores were used to evaluate postoperative clinical efficacy at 1 and 3 months after the operation, and to count the recurrence rates. All of these operations were performed between August 2017 and July 2020, and they were followed in the outpatient department for 12 months at least. Results Both of the groups showed significantly lower VAS and higher ODI scores at 1 month and 3 months post-operation, respectively, when compared with pre-operation. At 1 month after the operation, the restriction group performed lower VAS scores of low back pain compared with the non-restriction group, but this advantage disappeared at 3months post-operation. However, there was no statistical difference in the VAS scores of leg pain and ODI scores between the two groups, neither at 1 nor 3 months after the surgery. The recurrence rate is significantly lower in the restriction group than in the non-restriction group at a 12-month follow-up after the surgery. Conclusion Out-of-bed activity restriction in the early postoperative period of PELD could reduce LDH recurrence effectively, and it may relieve the low back pain to some extent. It has no benefit in the recovery of leg pain and functional rehabilitation.